Use of Geophysical and Remote Sensing Data for Assessment of Aquifer Depletion and Related Land Deformation - Othman, Abdullah; Sultan, Mohamed; Becker, Richard; Alsefry, Saleh; Alharbi, Talal; Gebremichael, Esayas; Alharbi, Hassan; Abdelmohsen, Karem (Surveys in geophysics, 2018)
An integrated approach [field, Interferometric Synthetic Aperture Radar (InSAR), hydrogeology, geodesy, and spatial analysis] was adopted to identify the nature, intensity, and spatial distribution of deformational features (sinkholes, fissures, differential settling) reported over fossil aquifers in arid lands, their controlling factors, and possible remedies. The Lower Mega Aquifer System (area 2 × 10 6 km 2 ) in central and northern Arabia was used as a test site. Findings suggest that excessive groundwater extraction from the fossil aquifer is the main cause of deformation: (1) deformational features correlated spatially and/or temporally with increased agricultural development and groundwater extraction, and with a decline in water levels and groundwater storage (− 3.7 ± 0.6 km 3 /year); (2) earthquake events (years 1985–2016; magnitude 1–5) are largely (65% of reported earthquakes) shallow (1–5 km) and increased from 1 event/year in the early 1980s (extraction 1 km 3 /year), up to 13 events/year in the 1990s (average annual extraction > 6.4 km 3 ). Results indicate that faults played a role in localizing deformation given that deformational sites and InSAR-based high subsidence rates (− 4 to − 15 mm/year) were largely found within, but not outside of, NW–SE-trending grabens bound by the Kahf fault system. Findings from the analysis of Gravity Recovery and Climate Experiment solutions indicate that sustainable extraction could be attained if groundwater extraction was reduced by 3.5–4 km 3 /year. This study provides replicable and cost-effective methodologies for optimum utilization of fossil aquifers and for minimizing deformation associated with their use.